Referral Demand of Patients in Pantai Cermin Public Health Center Langkat - Feti Novia Sari; Zulfendri; Sri Rahayu Sanusi (Britain International for Academic Research (BIAR) Publisher, 2020)
In 2017, the number of referrals issued by Pantai Cermin health center to Langkat District Hospital was 17.7% and the highest number in Langkat District. Referral cases more than 10% will increase hospital burden. This study aims to describe of referral cases at Pantai Cermin Health Center, Langkat. Aspect of referral type given 5 informants asked for referral to an internist, 2 informants asked for obstetricians, and one informant asked for referral to opthalmologist. Regarding who provided the referral, 6 informants stated that the referral was given by the doctor, and 2 informants stated that the referral was given by the midwife. In addition, the reason why the referral was given, 7 informants stated that the referral was given because the informant asked to be referred, and 1 informant stated that the referral was given because the equipment was not available at the public health center. Based on the results, it is recommended to pantai cermin health center to providing referral services in accordance with the applicable regulations and regularly monitoring of implementation of referrals system, and socialize to the community that referrals should be given according to the patient's medical need.